Pengaruh Strategi Concrete-Representational-Abstract (CRA) Terhadap Pemahaman Konsep Bangun Datar pada Peserta Didik Tunagrahita Ringan Kelas 4 SDLB di SLB Negeri Pembina Yogyakarta - Rahmi, Aulia (Jurusan Pendidikan Luar Biasa, 2022)
This study aims to apply the Concrete Representational Abstract (CRA) strategy in learning mathematics about flat shapes; namely the concept and shape of a square, rectangle and circle for mildly disabled students. Because flat shapes are objects that learners often find in everyday life. The subjects of the study were 2 female and 1 male mildly intellectual disability in class IV-A. The method used is Classroom Action Research (PTK) which aims to improve and improve the quality of learning through several actions, identification, planning, implementation, and reflection. The results showed that after this research was carried out there was an increase in the understanding and learning outcomes of students, this can be seen from the average test scores obtained by students increased in each cycle. The average pre-test score was 63, the first cycle was 83, the second cycle was 83, and the post-test was 87, meaning that there was a significant increase from the pre-test score of 63 to the post-test score of 87, with a steady increase after the first cycle. Thus, the use of the CRA strategy can improve the learning outcomes of students in class IV-A SLB Negeri Pembina Yogyakarta in mathematics. Class mastery and the application of the CRA strategy in teaching and learning activities are important factors in the success of learning.